Effects of Xanthan gum on rheological properties of Aloe vera-Moringa leaf juice blends - Matabura, Victor V; Rweyemamu, Leonard MP (Tanzania Journal of Science, 2021)
Understanding the impacts of hydrocolloid agents on the rheological properties of nutraceutical beverages like Aloe vera-moringa juice blend is very useful for functional properties and product stability. To this end, the effects of xanthan gum on rheological properties in Aloe vera-moringa leaf juice blends were investigated using a Brookfield rheometer. Aloe vera-moringa leaf juice blends were prepared and then incorporated with xanthan gum at different ratios (w/w) of 0.2%, 0.4%, 0.6%, 0.8%, and 1%. The results revealed that the viscosity of Aloe vera-moringa juice blend was strongly affected by the xanthan gum addition. The viscosity profiles depicted a decreasing trend in viscosity when a shear rate increased. The Aloe vera-moringa leaf juice blend changes from a Newtonian fluid to the non-Newtonian fluid as the xanthan gum fraction increases. Moreover, shear stress was observed to increase with increasing in xanthan gum concentrations. For quantitative analysis, both Power-law and Bingham model equations were fitted to experimental data to easily describe the flow behaviour of the Aloe vera-moringa leaf juice blends. The juices added with xanthan gum of 0.4% to 1% were found to show a shear-thinning behaviour, since the flow behaviour index, n < 1. This implies that the apparent viscosity decreases as the shear rate increases. Keywords: Aloe vera juice, Moringa leaf juice, Xanthan gum, Rheological property, Nutraceutical beverage.